2007
DOI: 10.1016/j.gene.2006.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two superoxide dismutases from Hydra vulgaris

Abstract: Apparent full-length cDNA sequences coding for manganese superoxide dismutase (HvMnSOD) and extracellular superoxide dismutase (HvEC-SOD) were isolated from Hydra vulgaris in order to understand their expression and 3D structures; and explore their possibility of being used as for biomarkers for environmental stress and toxicity. The deduced HvMnSOD protein consists of 219 amino acids of which first 21 amino acids constitute a presumed mitochondria-targeting signal peptide whereas HvEC-SOD protein consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Phylogenetic analysis of the N. vectensis SOD genes provides a glimpse into the diversification of SODs early in the evolution of animals and within the cnidarian lineage. Two CuZnSODs have previously been identified in the anemone A. viridis (Plantivaux et al, 2004), one in the hydrozoan H. vulgaris (Dash et al, 2007) and eight from an initial search of the genome of the coral A. digitifera (Shinzato et al, 2012). We have identified three CuZnSODs in N. vectensis, two of which are orthologs of the genes from A. viridis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Phylogenetic analysis of the N. vectensis SOD genes provides a glimpse into the diversification of SODs early in the evolution of animals and within the cnidarian lineage. Two CuZnSODs have previously been identified in the anemone A. viridis (Plantivaux et al, 2004), one in the hydrozoan H. vulgaris (Dash et al, 2007) and eight from an initial search of the genome of the coral A. digitifera (Shinzato et al, 2012). We have identified three CuZnSODs in N. vectensis, two of which are orthologs of the genes from A. viridis.…”
Section: Discussionmentioning
confidence: 93%
“…At the sequence level, searches of genomic and expressed sequence tag (EST) databases of the sea anemones Nematostella vectensis (Goldstone, 2008;Reitzel et al, 2008b) and Aiptasia pallida (Sunagawa et al, 2009), the coral Acropora digitifera (Shinzato et al, 2012) and the hydrozoan Hydra magnapapillata (Shinzato et al, 2012) have demonstrated the presence of multiple genes encoding antioxidant enzymes, including CuZnSODs, MnSODs, catalase, thioredoxins and glutathione peroxidases. Two CuZnSODs have been cloned from A. viridis (Plantivaux et al, 2004), and an extracellular CuZnSOD and a mitochondrial MnSOD have been identified in the freshwater hydrozoan Hydra vulgaris (Dash et al, 2007). Catalase has been cloned from A. viridis (Merle et al, 2007) and H. vulgaris (Dash and Phillips, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Hydra have the capacity to protect against oxidative stress since they contain two superoxide dismutase (SOD) genes (Dash et al, 2007). The SOD are of the type MnSOD which are principally found in the mitochondria and of the type CuZnSOD which is cytosolic in cells.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Previous research with cnidarians, primarily anthozoans, has characterized the expression of SODs and catalase (CAT) in response to environmental stress (Richier et al, 2003(Richier et al, , 2005Yakovleva et al, 2004;Dash et al, 2006Dash et al, , 2007Merle et al, 2007).…”
Section: Antioxidants and Metal Complexingmentioning
confidence: 99%